Media and its Role in Shaping Women’s Empowerment: A Study on Soap Opera Serials - Hmar, Emmanuel Lalrochang; Pathak, Jimoni (Journal of Advanced Research in Journalism & Mass Communication, 2020)
Indian Soap Operas are written, produced and filmed in India with characters Played by Indians and episodes broadcast on Indian television channels. They have also been broadcast not just within the territoriality of India but often many “serials” are also broadcast overseas. For example, the India soaps Operas are popularly seen in countries like Pakistan, the UK, US, South Africa and Australia and some parts of European countries. Without a doubt, Indian Soap Operas are often mass-produced under large production banners, with houses like Balaji Telefilms produced by Ekta Kapoor and Shobha Kapoor. Women’s empowerment with relation to the Impact of Indian Soap Operas through the Indian Cable system has been a debatable issue and this paper seeks to find answers to the dilemma of Social change evinced through this medium. The focus of the research is the tiny township of Silchar as a representative of the rest of the Indian woman’s mind and her choices. How to cite this article: Hmar EL, Pathak J. Media and its Role in Shaping Women’s Empowerment: A Study on Soap Opera Serials. J Adv Res Jrnl Mass Comm 2019; 6(3): 20-23.